Effect of Collaborative Writing Combined with Blog Online Learning on Indonesian EFL Learners’ Writing Skill across Motivation - Rizki Anugrah Putri Rahayu (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
Abstract: This study aims to investigate collaborative writing combined with blog online learning on the writing skill of Indonesian English foreign language (EFL) learners’ across their motivation. This research included a quasi experimental with the comparative time series. A quasi experimental study was employed by involving 61 learners of Senior High School. This research applied in into two groups: experimental and control. The treatment was conducted at 7 sessions, including the pre-test and post-test. The scores of pre-test and post-test in writing were used as a base of quantitative data analysis whereas the learners’ responses to motivation questionnaire were used to categorize their motivation. The result revealed that the collaborative writing combined with blog online learning on the writing was effective to enhance the learners’ writing skill. In addition, to apply the combination of collaborative writing and online blog learning, teacher should not worry about different levels of motivation among students where the students were motivated to use language.